Architectural design keywords of inception space / Muhammad Heru Arie Edytia, Zulhadi Sahputra and Mirza - Muhammad Heru, Arie Edytia; Zulhadi, Sahputr; Mirza, Mirza (Universiti Teknologi MARA, Perak, 2019)
This paper explains the idea of inception space from Inception (2010), a movie directed by Christopher Nolan, to explore the inception space potential in designing architectural space. Inception space is an architectural space design mechanism that translates the essential experience of space users as an effort to implant idea in the form of positive emotions. In other words, the architectural space is a medi-um of inception to a space user or a target (mark). The main purpose of inception space design is to affect the target (mark) by planting the idea 'secretly'. The target is unaware of the intervention and considers the idea presented itself. This process becomes the beginning of an idea to grow in one's mind the begin-ning of mindset and behavior change. In other words, architects or planners can apply this mechanism to design and influence users so that the design success rate can be improved. The main design keywords as part of the inception process are perception, memory, scenario, layer, and labyrinth. The development of design methods of inception space can be explored and applied to different targets and contexts by apply-ing these design keywords. For example, this design mechanism can be applied to people with dementia who experience memory and visuospatial deficit through wayfinding programming.